Analysis of Financial Risk Profiles and Enterprise Risk Management Frameworks in Transit-Oriented Development Property Companies - Aurelia Widya Astuti (Al-Makki Publisher, 2025)
Indonesia's property industry faces increasing complexity of financial risks in the post-pandemic era, especially Transit-Oriented Development (TOD)-based companies that integrate property development with mass transportation infrastructure. This study aims to analyze the financial risk profile of PT Adhi Commuter Properti Tbk and identify an appropriate Enterprise Risk Management framework to manage the risk of TOD property companies. The research adopts a quantitative approach with a case study design, analyzing the audited financial statements for the period March 31, 2025 through a comprehensive financial ratio analysis that includes four dimensions: profitability, debt repayment, operational efficiency, and growth strategy. The results of the study revealed an alarming financial risk profile with a Net Profit Margin of only 0.02%, Return on Assets 0.000236%, Return on Equity 0.000622%, a very low Quick Ratio at 9.94%, a high Debt to Equity Ratio of 1.64, an Asset Turnover of 1.02%, and a decrease in net profit of 99.77%. The findings confirm that the company faces significant liquidity risks, excessive leverage, low profitability, and weak operational efficiency that require urgent strategic intervention. The research identifies the need for the implementation of the COSO Enterprise Risk Management and Integrated Risk Management framework tailored to the unique characteristics of the TOD. Practical implications include restructuring capital structures, improving operational efficiency, strengthening liquidity management, and developing an early warning system based on Big Data technology to proactively detect potential financial distress and increase the financial resilience of TOD property companies in Indonesia.